Lidar reveals distinct insect daily activity and diversity between habitats - Doria Yamoa, Assoumou S; Kouakou, Benoit K; Gbogbo, Adolphe Y; Runemark, Anna; van Klink, Roel; Zoueu, Jeremie T; Brydegaard, Mikkel (Scientific Reports, 2025)
Entomological lidar can provide rapid, non-intrusive assessment of insect abundance, diversity and composition, and has the potential to shed light on species specific preferences for habitats or environmental conditions. However, few studies have to date demonstrated comparisons of insect diversity and abundance across sites using photonic methods. Here, we present a first comparative entomological lidar study spanning different habitat types, investigating if the method can uncover consistent differences in insect diversity and composition. Using a simple, robust and parameter free estimation of entomological signal diversity, we recover the largest total number of insect observations (1,716,362), the highest daily number of observations (346,581) and the highest number of clusters distinguishable from noise (353) reported to date. We demonstrate consistent differences between four sites in terms of abundance, diversity, composition, range distributions and daily activity patterns. We critically discuss possible biases, constraints and future challenges for physicists and ecologists employing entomological lidar for diversity estimation.
© 2025. The Author(s).